1985
DOI: 10.1111/j.1476-5381.1985.tb11084.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet desensitization induced by arachidonic acid is not due to cyclo‐oxygenase inactivation and involves the endoperoxide receptor

Abstract: 1Human platelets pre-exposed to arachidonic acid (AA) (0.1-1 mM) or to the endoperoxide analogue U46619 (1-3 tLM) and then washed and resuspended, failed to respond with aggregation or secretion to a second challenge by either agonist. The response to thrombin at low (0.04-0.1 u ml-') but not at high (2.5 u ml ') concentrations was also inhibited by pre-exposure to AA and U46619. 2 The ability of platelets to synthesize thromboxane (Tx) B2 from AA or upon challenge with thrombin persisted despite platelet dese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This schema is consistent with the notion that there are separate platelet TXA2 and endoperoxide (PGH2) receptors (3, 4) with distinct functions. As suggested by Carmo et al, endoperoxides may be responsible for irreversible platelet aggregation and secretion whereas TXA2 may cause initial platelet shape change and cellular approximation (3 (13). Antagonists bind with less specificity than do agonists and, in general, with greater capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This schema is consistent with the notion that there are separate platelet TXA2 and endoperoxide (PGH2) receptors (3, 4) with distinct functions. As suggested by Carmo et al, endoperoxides may be responsible for irreversible platelet aggregation and secretion whereas TXA2 may cause initial platelet shape change and cellular approximation (3 (13). Antagonists bind with less specificity than do agonists and, in general, with greater capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the indistinguishable effects of these agents upon platelets, a common notation has been to label their combined putative receptor as TXA2/PGH2 (2). However, some studies have suggested that separate platelet receptors exist for the endoperoxide PGH2 and TXA2 (3,4). The thromboxane receptor has been postulated to mediate platelet shape change and the endoperoxide receptor has been postulated to mediate aggregation (3).…”
mentioning
confidence: 99%
“…As described (Carmo et al, 1985), preincubation of washed platelets with U46619 (0 . 3 mM) led to platelet desensitization to U46619 itself, whereas the response to thrombin (1 IU/ ml) remained similar to control platelets (Fig 1).…”
Section: Desensitization Of Pgh 2 /Txa 2 Receptor By U46619 and Sensimentioning
confidence: 99%
“…3 mM) led to platelet desensitization to U46619 itself, whereas the response to thrombin (1 IU/ ml) remained similar to control platelets (Fig 1). This homologous desensitization by and to U46619 occurred at a site sensitive to PGH 2 /TxA 2 receptor antagonists (Carmo et al, 1985). The cAMP levels in control and desensitized platelets were evaluated in parallel at different times of cell incubation with PGI 2 (0 .…”
Section: Desensitization Of Pgh 2 /Txa 2 Receptor By U46619 and Sensimentioning
confidence: 99%
See 1 more Smart Citation